2010
DOI: 10.1124/mol.109.062299
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Affinity States of cGMP-Specific Phosphodiesterase for Sildenafil Inhibition Defined by cGMP-Dependent and cGMP-Independent Mechanisms

Abstract: cGMP-specific phosphodiesterase (PDE5) has become a target for drug development for the treatment of a number of physiological dysfunctions, affected by changes in the cGMP/ cGMP-dependent protein kinase (PKG) signaling pathway. PDE5 has two highly homologous regulatory domains, GAF-A and GAF-B. We showed previously that PDE5 could be converted from a low-activity (nonactivated) state to a high-activity state upon cGMP binding to the GAF-A domain with higher sensitivities toward sildenafil (EMBO J 22: 469 -478… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…The data questioned the functional role of cGMP. Because it is reported that sildenafil sensitivity of PDE5 can be regulated by cGMP-independent mechanisms ( 32 ), the role of PDE5 and its dependence on cGMP needs further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…The data questioned the functional role of cGMP. Because it is reported that sildenafil sensitivity of PDE5 can be regulated by cGMP-independent mechanisms ( 32 ), the role of PDE5 and its dependence on cGMP needs further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study described a new ‘super‐high’ sensitivity state for sildenafil inhibition (Rybalkina et al ., 2010) raising the question whether the different sensitivity states are related to the two conformations described above. As the two sensitivity states were observed only in the non‐stimulated enzyme whereas the two conformations described in our study were observed at non‐stimulating (0.03 µM cGMP) and stimulating cGMP concentrations (100 µM), the sildenafil sensitivity states appear to be distinct from the two activity states.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, CO and exogenous compounds such as 3-(5 0 -hydroxymethyl-2 0 -furyl)-1-benzylindazole (YC-1) and 3-(4-amino-5-cyclopropylpyrimidin-2-yl)-1-(2-fluorobenzyl)-1H-pyradazolo [3,4-b]pyridine (BAY 41-2272) synergistically activate sGC to levels approximately similar to those induced by NO [88,89]. Such sGC induction leads to the increase of the cGMP level and to the activation of the cGMP-dependent protein kinase (PKG) phospho-transferase activity, thus affecting several cellular functions based on ion channel, phosphodiesterase, and protein kinase actions [77,80,[90][91][92][93][94][95].…”
Section: Co Signalingmentioning
confidence: 99%